HAK ULAYAT ATAS WILAYAH PESISIR BAGI BENDEGA PASCA DITETAPKANNYA PERDA 11/2017 (Studi Di Desa Adat Tuban) - Trisnadiasa, I Nyoman Agus; Sulistyawati, Ni Putu Yunika; Arthadana, Made Gede (VYAVAHARA DUTA, 2020)
Recognition of the exixtence of bendega as a traditional instituion in the Province of Bali is getting stroger after the issuance of Peraturan Daerah Provinsi Bali Nomor 11 tahun 2017 tentang Bendega. Even though i tis located as a traditional institution, bendega still given space to innovate in economic activities without ignoring the value of local wisdom. In Desa Adat Tuban, i tis found that there are groups of local people who are still pursuing the fishing profession. In addtion, this community group is also innovating in economic activities by utilizing the coastal areas which are Forest Park Conservation area Tahura.The objectives of this study are (1) the find out and analyze the legal position of fishing groups in Desa Adat Tuban after issuance of Peraturan Daerah Provinsi Bali No 11 Tahun 2017 tentang Bendega; (2) knowing and analyzing the stateâ€™s recognition of fishermen groups in Desa Adat Tuban as the legal subject in charge of management of coastal areas.This research is an empirical legal research. Using primary data obtainedÂ  hrough observation an interview techniques. The secondary data is the collectedthorugh a literature study. All data collected is the analyzed qualitatively. The output of this research is a secintific journal with ISSN. In connection with the TKT research, the target that can be achieved in this study is TKT 3 in accordance with the indicators that have been determined.